A Review on the Radioprotective Activity of organogermanium and Organosilicon Compounds. Issue 1 (1999) - Rima Rima, Ghassoub Ghassoub; Satgé Satgé, Jacques Jacques; Dagiral Dagiral, Rodolphe Rodolphe; Lion Lion, Claude Claude; Sentenac-Roumanou Sentenac-Roumanou, Henri Henri; Fatôme Fatôme, Marc Marc; Roman Roman, Vincent Vincent; Laval Laval, Jean-Denis Jean-Denis
Abstract : The present review describes the work carried out during the last 20 years in the field of the radioprotective activity and toxicity of several classes of organosilicon and organogermanium compounds (i.e. metallathiazolidines, metalladithioacetals, metallatranes and germathianes).